Verbal Divorce between Consideration, Inconsideration, and its Impact on Marital Relationship - Dwairi, Orwah Nassir; al- Shorofat , Jihad Salim (Dirasat: Shari'a and Law Sciences, 2021)
The present study aims to address the verbal restrictions on divorce to be considered as valid in modern family law and classical Fiqh schools of thought. These verbal restrictions can be employed to play a crucial role in reducing high divorce rates. Fiqh opinions of Muslim scholars regarding types of verbal divorce forms are considered legislative sources and legal references not only for Muftis, judges and experts dealing with cases of divorce but also for any Muslim that has a firm intention to divorce his wife properly. In this study, legal articles regarding verbal restrictions on divorce are analysed to investigate their compatibility with Fiqh opinions as well as their impact on reducing divorce rates. This study has come to the conclusion that while it is highly important to reduce divorce rates based on verbal restrictions, divorce rates can also be handled by establishing effective legal treatments and deterrent legal measures for those husbands who divorce their wives in an inappropriate way.